Key indicators of the financial stability of the national economy in the conditions of external threats - Чкан, Ірина Олександрівна; Chkan, Iryna (Харків : ДБТУ, 2024)
EN: The current state, trends in the development of the world economy and the financial system indicate an increase in the risks of the emergence and development of crisis phenomena. Despite the rapid pace of digitization of production processes, strengthening of their cyber protection, digitization of life, etc., with the onset of unpredictable events of a macroeconomic nature, it becomes obvious to ensure the financial stability of the economy. Existing and possible threats of internal and external origin temper the national economy enable the country to minimize the negative impact of shocks and show steadily growing economic dynamics in the future. In fact, the financial security of the country should be determined by the result of very real calculation processes, taking into account the actions caused by the conflict of interests: the debt burden artificially imposed on the state; a loan obtained on the basis of false information, which no one is going to return; claim for payment of insurance compensation for a falsified insurance case, etc.
Keywords: financial stability of the national economy; financial instability; ensuring the financial capacity of the state budget; confirming the trust of international partners